1991
DOI: 10.1152/ajpendo.1991.261.4.e425
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evidence for hepatic autoregulation during FFA-stimulated gluconeogenesis in normal humans

Abstract: To examine the effect of increased gluconeogenesis [by increasing free fatty acids (FFA)] on hepatic glucose output (HGO) and on the first substrate (glucose) cycle, a primed continuous infusion of [2-3H]- and [6-14C]glucose was infused to isotopic steady state in 12 normal male volunteers after an overnight fast. Blood samples for the determination of glucose specific activity were obtained before and after an infusion of saline (n = 6) or 10% Intralipid and heparin (90 mU.kg-1.min-1, n = 6). Plasma FFA (593.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
69
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 33 publications
5
69
1
Order By: Relevance
“…It has been suggested that increased gluconeogenesis would not result in increased HGP since infusion of intralipid [47] or lactate [48] in healthy subjects has been shown to increase the rate of gluconeogenesis without increasing HGR This has been interpreted as showing autoregulation of HGP by the liver. In the NZO mouse however, increased gluconeogenesis is associated with increased HGR This does not necessarily indicate the failure of an autoregulatory mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that increased gluconeogenesis would not result in increased HGP since infusion of intralipid [47] or lactate [48] in healthy subjects has been shown to increase the rate of gluconeogenesis without increasing HGR This has been interpreted as showing autoregulation of HGP by the liver. In the NZO mouse however, increased gluconeogenesis is associated with increased HGR This does not necessarily indicate the failure of an autoregulatory mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of FFAs to stimulate gluconeogenesis is well established (37)(38)(39). However, the effects of FFAs on hepatic glucose release are less certain.…”
mentioning
confidence: 99%
“…However, the effects of FFAs on hepatic glucose release are less certain. Most (10,15,16,22,40), but not all (39), studies indicate that elevated FFAs impair insulin-induced suppression of endogenous glucose production. Although the liver is generally assumed to be the source of the increased glucose release, this has yet to be established in humans because only the effects of FFAs on total-body (commonly referred to as endogenous) glucose production has been measured.…”
mentioning
confidence: 99%
“…These effects of lipid substrates have also been observed in vivo in humans. Infusion of a triglyceride emulsion stimulated gluconeogenesis from lactate in healthy volunteers (50). However, as observed during infusion of gluconeogenic substrates, such a stimulation of gluconeogenesis failed to stimulate endogenous glucose production.…”
Section: Effects Of Nutrients On Endogenous Glucose Productionmentioning
confidence: 86%